Early readmission and mortality in acute exacerbation of chronic obstructive pulmonary disease with community-acquired pneumonia - Shin, Beomsu (Chron Respir Dis, 2018)
Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are important causes of hospital admission and mortality. Pneumonia is a major contributor to hospitalization for AECOPD and has a close relationship with poor outcomes. We performed a prospective cohort study to evaluate the prognosis of AECOPD patients with or without community-acquired pneumonia (CAP) who hospitalized from January 2012 to December 2015. We investigated mortality and readmission rates within 6 months after the first admission between two groups and analyzed the difference of survival rate according to readmission duration (≤30 vs. >30 days) or intensive care unit (ICU) treatment. Total 308 AECOPD patients (134 with CAP and 174 without CAP) were enrolled. The mean age was 72.3 ± 9.5 years old, and 235 patients (76.3%) were male. The 180-day mortality was higher in AECOPD with CAP than without CAP (24.6% vs. 13.2%; hazard ratio (HR): 1.982; 95% CI: 1.164–3.375; p = 0.012). However, readmission rate showed no significant difference between two groups (51.5% vs. 46.6%; HR: 1.172; 95% CI: 0.850–1.616; p = 0.333). It showed a significantly lower survival rate in AECOPD with CAP rather than without CAP when were readmitted within 30 days (HR: 1.738; 95% CI:1.063–3.017; p = 0.031). According to ICU treatment, survival rate was not significantly different between two groups. Multivariate analysis revealed the readmission within 30 days (p  <  0.001), serum hemoglobin concentration (p  =  0.010), and albumin level (p =  0.049) were significantly associated with 180-day mortality of AECOPD with CAP. AECOPD with CAP showed lower survival rate than AECOPD without CAP during 6 months. Early readmission within 30 days was significantly associated with an increased risk of mortality.